(untitled) (Research, Society and Development, 2022)
The purpose of any drug delivery system is to deliver appropriate therapeutic amounts of drugs to the body in order to achieve and maintain the desired concentration of the administered substance. The aim of this work to analyze innovations in drug delivery systems by oral and transdermal route by the pharmaceutical industry. It is integrative review of literature, analyzing studies in some databases such as in PubMed, SciELO and LILACS, with the descriptors: drug delivery systems, pharmaceutical industry, hormones, oral and transdermal. The papers selected for the study range from 2000 to 2021, excluding duplicate studies and those that were not related to the topic. The research initially identified 5360 studies, being 5336 of those papers excluded after the application of exclusion criteria. A greater number of studies with the descriptor hormones was observed, substantially greater in the range from 2006 to 2011. There was a greater predominance of transdermals than oral in which concerns selected studies. This information reinforces, therefore, the great advantage of treatments with these types of systems, as they improve the patient’s therapy bringing an adequate cure or palliative. In addition, it is also noted that a greater incentive is needed to study these systems orally, providing new insulin therapies, for example, orally, bringing more adherence, without the routine stings.